Three dimensional finite-differential simulation of the wave field taking sphericity of the Earth into account - A.O. Verpakhovskaya; V.N. Pilipenko (Геофизический журнал, 2020)
Three dimensional modeling of the wave field makes possible to obtain a concept on distribution of seismic waves in geological medium with different complexity of its structure. The location of the source of fluctuations may be defined in this case at any depth. Therefore, three dimensional modeling of the wave field may be used while solving the problems of seismology related to the nature of strains in the Earth’s interior, while studying the dangerous phenomena of endogenous origin as well as in the case of studies of the deep structure of the Earth, the boundaries of its division and its tectonic structures.